Alginate-cysteine conjugate: antimicrobial hydrogel from natural source - Soares, Tatiane Araujo; Torres, André Henrique Furtado [UNESP]; Dorm, Bruna Carolina; Amaral, André Capaldo; de Souza Nossa, Tamires; Trovatti, Eliane (Springer Nature, 2024)
Microbial infections spreading represents a challenging scenario worldwide, with remarkable demand for attention in food and heath fields. An increase in studies for the development of new biomaterials with the aim of decreasing or avoiding bacterial infections has been arising, and the natural polymers have been the focus of some studies. Alginate is an abundant natural polymer with potential for chemical modifications based on its chemical structure and, to the best of our knowledge, it was not modified for antimicrobial activity. This study aims to prepare a new biomaterial by chemical modification of alginate coupled with the cysteine, aiming to infer intrinsic antimicrobial activity to the resulting material, and also, situ gelation capability by the formation of disulfide bonds. The polymers were characterized by FTIR, NMR, thermal analysis, cross-linking test, rheological analysis, hydrolytic degradation, microbiological test (against E. coli and S. aureus) and cytotoxicity. The results of the chemical characterization, as evidenced by FTIR and NMR, indicated the success of the reaction and the increase in the viscosity of alginate-Cys due to the cross-linking of the material. The results showed no toxicity and demonstrated antimicrobial activity against the studied bacteria, indicating their potential for the development of materials for applications in the confection and coating of medical devices, aiming to decrease or avoid infections.
Keywords: Alginate; Antimicrobial activity; Cysteine; E. Coli; S.aureus